Challenges to Necessity-Driven Nascent Entrepreneurship - Dzingirai, Mufaro (2022)
Necessity-driven nascent entrepreneurship, which often associated with new firm creation and innovation, has emerged as a topical issue in entrepreneurship scholarship across the globe in recent times especially in developing countries. While the increase in necessity-driven nascent entrepreneurs appears to be widely regarded as a powerful tool for the reduction or elimination of unemployment and poverty worldwide, insufficient attention has been given to the challenges faced by necessity-driven nascent entrepreneurs. With this literature gap in mind, this chapter aims at providing a comprehensive understanding of challenges faced by necessity-driven nascent entrepreneurs. The research establishes six challenges, namely, personal or family problems, lack of entrepreneurial self-confidence, lack of information, lack of entrepreneurial mentorship, legal and regulatory issues, and lack of adequate personal funds. The recommendations to deal with these challenges are proffered and the suggestions for further study are captured.